Microbiome dysbiosis in depression: a systematic review - Arzmi, Mohd Hafiz; Rismayuddin, Nurul Alia Risma; Wan Mohd Kamaluddin, Wan Nur Fatihah; Ismail, Ahmad Faisal; Zakaria, Rozanizam; Mohamad, Noor Afifah Hanin; Mokhtar, Munirah (Fakulti Perubatan dan Sains Kesihatan, UPM, 2021)
The objective of the study is to determine the role of microbiome dysbiosis in depression, with the hypothesis that dysbiosis involves in depression. PubMed, Science Direct and Scopus databases were used to identify the relevant studies which fulfilled the eligibility criteria. The searches were limited from January 2015 to July 2020. Joanna Briggs Institute (JBI) Critical Appraisal Tools was used for quality assessment of the studies. This review was performed according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA-P) 2015 proto- col guidelines. Initially, 1297 studies were identified. Of these, only three studies were included in the final synthesis. The studies were categorised as “high” quality. Dysbiosis of the gut microbiome, particularly by Faecalibacterium, Dialister, Acetivibrio, Collinsella, and Odofibacter, has been involved in depression. Treatment using probiotics such as Lactobacillus acidophilus, Bifidobacterium longum and Enterococcus faecalis was suggested to promote a balanced gut microbiome. Microbiome dysbiosis may involve in depression, thus supporting the hypothesis of the present study. However, no consensus was obtained to conclude which bacterial taxa are mostly relevant to depression.